State, federalism and educational policies: implications in brazilian education (Research, Society and Development, 2018)
The article discusses the relationship between state and federalism as a political and administrative organizational form of the state and its implications in Brazilian educational policy. For that, we follow the analysis of the concepts of State, federalism, and educational policies from the classics of Machiavelli (2001), Locke (1998), Rousseau (1999), Hamilton, Jay and Madison (2003), Abrucio Arretche (1996), among others. Therefore, we see that the new Brazilian federalism based on the model proposed by the American Constitution brings the local powers – the municipalities – as new agents within the educational policy and the collaboration regime as a means of effecting cooperative federalism in Brazil. We conclude that the federalism, in Brazilian model, presents itself as demos constraining the national sub-governments.